Screening and Identification of Human Endogenous Retrovirus-K mRNAs for Breast Cancer Through Integrative Analysis of Multiple Datasets - Wei, Yongzhong; Wei, Huilin; Wei, Yinfeng; Tan, Aihua; Chen, Xiuyong; Liao, Xiuquan; Xie, Bo; Wei, Xihua; Li, Lanxiang; Liu, Zengjing; Dai, Shengkang; Khan, Adil; et al. (Frontiers in Oncology, 2022)
Objective: Human endogenous retroviruses (HERVs) make up 8% of the human genome. They are biologically active elements related to multiple diseases. HERV-K, a subfamily of HERVs, has been associated with certain types of cancer and suggested as immunologic targets in some tumors. Their expression levels in breast cancer (BCa) have been studied as biomarkers and immunologic therapeutic targets. However, HERV-K has multiple copies in the human genome, and few studies determine the transcriptional profile of the HERV-K copies across the human genome for BCa. Methods: We firstly created 91 HERV-Ks indexes with entire proviral sequences as a reference database. Nine raw sequencing datasets with 251 BCa and 131 control samples were mapped to this database by Salmon software. The differential proviral expression across several groups was analyzed by DESeq2 software. Results: First, by clustering each dataset, we demonstrated that these 91 HERV-Ks proviruses could well cluster the BCa and control samples when the normal controls were normal cells or health donor tissues. Second, several common HERV-K proviruses that closely related with the risk of BCa were firstly significantly differentially expressed (Padj < 0.05 and absolute log2FC > 1.5) in the tissues and cell lines. Additionally, almost different HERV-K proviruses indicated higher expression in BCa tissue than healthy donors. Especially, an exciting result was that we first found the expression of 17p13.1 provirus that located with TP53 should regulate TP53 expression in ER+ and HER2+ BCa. Conclusion: The expression profiling of these 91 HERV-K proviruses can be biomarkers to separate the BCas and healthy controls. Some proviruses, especially 17p13.1, were strongly associated with the risk of BCa. These results suggest that HERV-Ks expressing profiles may be appropriate biomarkers and targets for BCa.